2013
DOI: 10.1111/twec.12068
|View full text |Cite
|
Sign up to set email alerts
|

Home Firm Performance After Foreign Investments and Divestitures

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…In case of industry level studies and firm level studies there is some consensus in their results obtained. Most of the studies have found a complementary relationship (Kim, 2000;Head and Ries, 2001;Lim and Moon, 2001;Lipsey and Ramstetter, 2003;Chow, 2012;Kang, 2012;Engel and Procher, 2013). The number of industries with complementary relationship is more than the negative ones (Forte and Silva, 2017).…”
Section: Impact Of Outward Fdi On Home Country Exportsmentioning
confidence: 99%
“…In case of industry level studies and firm level studies there is some consensus in their results obtained. Most of the studies have found a complementary relationship (Kim, 2000;Head and Ries, 2001;Lim and Moon, 2001;Lipsey and Ramstetter, 2003;Chow, 2012;Kang, 2012;Engel and Procher, 2013). The number of industries with complementary relationship is more than the negative ones (Forte and Silva, 2017).…”
Section: Impact Of Outward Fdi On Home Country Exportsmentioning
confidence: 99%